Information System of Graduation in Administration and Academic Bureau Soegijapranata Catholic University - Albertus Dwiyoga Widiantoro (SISFORMA, 2015)
The development of online graduation system becomes a necessity because it is expected that the graduation registration system can be conducted and finished fast and the data can be straored safelyThe system helps in the process of administration in terms of inspection files and financial report by the authorities more quickly. From the student side of the system is very helpful in checking the online registration process.